2023
DOI: 10.3390/met13020423
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Welding Mode Parameters on the Operational Properties of Flexible Compensating Elements Made of Austenitic Stainless Steels

Abstract: The paper investigates the effect of welding mode parameters on the uniformity of the deformation capacity of AISI 316 austenitic steel samples, namely, the influence of the welding current and purging gas consumption on the samples’ ability to perceive the force of cold cupping. Punch diameters of 3 and 8 mm were employed for the Erikson test to establish the dependence of the purge gas flow rate on the depth of the hole before the formation of cracks. The conducted metallographic studies confirmed an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…In [2], the influence of consumable electrode welding mode parameters in shielding gas on the deformation of AISI 316 austenitic steel samples was studied; additionally, the influence of the welding current and purging gas consumption on the samples' ability to perceive the force of cold cupping was studied. The conducted metallographic studies confirmed an increase in the homogeneity of the dendritic structure in the weld zone due to the redistribution of heat input, as well as the absence of uneven grains and a decrease in the spread of grain sizes, which were in the range of 0.068-0.045 mm.…”
Section: Contributionsmentioning
confidence: 99%
“…In [2], the influence of consumable electrode welding mode parameters in shielding gas on the deformation of AISI 316 austenitic steel samples was studied; additionally, the influence of the welding current and purging gas consumption on the samples' ability to perceive the force of cold cupping was studied. The conducted metallographic studies confirmed an increase in the homogeneity of the dendritic structure in the weld zone due to the redistribution of heat input, as well as the absence of uneven grains and a decrease in the spread of grain sizes, which were in the range of 0.068-0.045 mm.…”
Section: Contributionsmentioning
confidence: 99%